Gender Equality And Bank Earning Management: Does Choosing Women Impact Increased Bank Income? - Hidayat, Deny; Pradani, Tiara; Anggraini, Winda Ayu (Jurnal Ekonomi, 2024)
This study investigates the relationship between gender diversity in leadership and income diversification within the Indonesian banking sector, with earnings management as a moderating factor. Focusing on banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023, the research evaluates how board diversity—specifically gender, age, educational background, and financial expertise—affects income diversification, as measured by the Herfindahl-Hirschman Index (HHI). Gender diversity is posited to influence income stability positively, as female leaders often contribute to more ethical and conservative financial decisions, which may stabilize income sources. Hierarchical regression analysis, moderated by earnings management variables, was employed to test these relationships. Results indicate that gender diversity is significantly associated with income concentration, while the impact of age, education, and financial expertise diversity on income diversification is not statistically significant. Earnings management moderates the relationship between financial expertise and income diversification, suggesting a conditional effect where high earnings management strengthens the income concentration associated with financial expertise. These findings contribute to the ongoing discourse on ethical leadership, financial stability, and gender diversity in banking governance.